Clinico-morphological correlations in the categorization of holes between the ventricles - Friedman Brad; Hlavacek Anthony; Chessa Karen; Shirali Girish; Corcrain Eowyn; Spicer Diane; Anderson Robert; Zyblewski Sinai (Wolters Kluwer Medknow Publications, 2010)
Controversy still exists in the categorization of holes between the ventricles, although they are the most common congenital cardiac malformation. Advanced imaging techniques such as three-dimensional echocardiography and computed tomographic angiography offer superb anatomical details of these defects. In this review, we have sought to collate the features highlighted in different categorizations and identify their similarities, but also emphasize their differences. We hope that an analysis of this type, now achievable during life, using advanced imaging, might lead to the appearance of a unified system for diagnosis and description of holes between the ventricles.